PRODUKSI, ISOLASI DAN KARAKTERISASI ENZIM DEKSTRANASE dari Arthrobacter sp. B7 - Afaf Baktir; Untung Murdiyatmo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
Dextranase enzyme has been purified and characterized from Arthrobacter sp. B7. This enzyme was purified from the culture supernatant of Arthrobacter sp. B7 by procedure of native PAGE. The molecular size of the enzyme was estimated 72,5 kDa by SDS-PAGE. The N-terminal amino acid sequence of this enzyme determined using Edman degradation techniques were APVTADVGNLHT. SDS-PAGE and native-PAGE analysis revealed that the enzyme molecule consisted of one sub-unit.